The Effect of Ispring Suite Learning Media on Student Achievement in Fiqh . Subjects - Indah Miftahul Umam; Siti Sulaikho (AT-TURATS, 2021)
This Research aim is knowing the properness of Ispringsuite based android system in Fiqh Material for The first grade in MTSN 14 Megaluh, Jombang. This research using Design Based Research in Brog and Gall Approach. The research Instrument is form as questionnaire validation of Material exprt, linguistic expert, IT expert, in other hands there is also questionnaire validation for students response. The assessment is conducted by classroom mean Score, Likert Scale. The result from the material expert is 81, 91% which claim as extemely proper, from the linguistic expert is 80,25%, which named by verry proper. Beside, the score from IT expert is 70.61% which state as proper category. And the score from the students is around 90%, Which state as extremely proper. In conclusion, Ispring suite Learning Media based Android System in Fiqh Material is Proper to use.